An Unconditionally Stable Positivity-Preserving Scheme for the One-Dimensional Fisher–Kolmogorov–Petrovsky–Piskunov Equation. (19th October 2021) - Kim, Sangkwon; Lee, Chaeyoung; Lee, Hyun Geun; Kim, Hyundong; Kwak, Soobin; Hwang, Youngjin; Kang, Seungyoon; Ham, Seokjun; Kim, Junseok
Abstract : In this study, we present an unconditionally stable positivity-preserving numerical method for the Fisher–Kolmogorov–Petrovsky–Piskunov (Fisher–KPP) equation in the one-dimensional space. The Fisher–KPP equation is a reaction-diffusion system that can be used to model population growth and wave propagation. The proposed method is based on the operator splitting method and an interpolation method. We perform several characteristic numerical experiments. The computational results demonstrate the unconditional stability, boundedness, and positivity-preserving properties of the proposed scheme.